La regola e il progetto Un approccio bioregionalista alla pianificazione territoriale - Magnaghi, Alberto (Territori, 2014)
The territory is constantly being torn by thousands of conflicting interests and, as a common good, it is in growing need of a unitary planning, suitable for the people living, working and consuming in it: an amount of suitability including urban places, city networks, rivers, valleys, agricultural areas and coastal hinterlands. Compared to the architectural and urban project, the territorial project has much more episodic and sectoral disciplinary rules. This volume is the Tuscan outcome of a national research on the "territorial project", and provides the concept of urban bioregion as a methodology which can integrate analyses and projects on: the environmental prerequisites of the settlement, the reconfiguration of synergies between city and countryside, the polycentric rebalancing of urban systems, locally-based economic and energy systems, forms of self-government for local and self-sustainable development starting from the rules for the enhancement of the territory's heritage.